TOWARDS SINGLE EUROPEAN SKY ? MUSING ON (POSSIBLE) CROSS-BORDER ACQUISITIONS OF ANS PROVIDERS IN EUROPE - Tomová, Anna (Doprava a spoje, 2012)
In this paper we analyse the European Union air navigation services providers focusing on commercialisation and privatisation, reflection of these processes in chosen performance indicators as well as broader threads of (possible) cross-border acquisitions of ANS providers in Europe using information on NATS privatisation. We conclude the paper findings with statement that prospective cross-border acquisitions of ANS providers in Europe are not feasible mainly from political reasons and therefore the main drivers towards goals of Single European Sky will rest upon the EU harmonisation legislation.